2017
DOI: 10.1007/s11904-017-0362-z
|View full text |Cite
|
Sign up to set email alerts
|

The Vaginal Microbiome and its Potential to Impact Efficacy of HIV Pre-exposure Prophylaxis for Women

Abstract: Purpose of review This review describes existing evidence addressing the potential modulation of PrEP products, specifically 1% tenofovir (TFV) gel and oral tenofovir-based PrEP, by vaginal dysbiosis and discusses future considerations for delivering novel, long-acting PrEP products to women at high-risk for vaginal dysbiosis and HIV. Recent findings We describe results from analyses investigating the modification of PrEP efficacy by vaginal dysbiosis and studies of biological mechanisms that could render Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…On the other hand, the relationship between bacterial vaginosis (BV) and the possible efficacy of microbicides has been a focus of attention. A recent study revealed that the lack of effectiveness in TFV gel microbicide CAPRISA 004 clinical trial was due to the present BV and to the drug depletion via bacterial metabolism [106,107]. These results support the idea that G2-S16 dendrimer represents a safe and powerful candidate to step into HSV-2 treatment clinical trials (manuscript under preparation).…”
Section: Prevention Of Vaginal Hsv-2 Infection In Presence Of G2-s16 supporting
confidence: 59%
“…On the other hand, the relationship between bacterial vaginosis (BV) and the possible efficacy of microbicides has been a focus of attention. A recent study revealed that the lack of effectiveness in TFV gel microbicide CAPRISA 004 clinical trial was due to the present BV and to the drug depletion via bacterial metabolism [106,107]. These results support the idea that G2-S16 dendrimer represents a safe and powerful candidate to step into HSV-2 treatment clinical trials (manuscript under preparation).…”
Section: Prevention Of Vaginal Hsv-2 Infection In Presence Of G2-s16 supporting
confidence: 59%
“…Recent studies have begun to provide important information demonstrating that gut microbes can affect the efficacy of several drugs [ 61 ]. Klatt et al [ 37 ▪▪ ] recently demonstrated that the microbiota in the female reproductive tract (FRT) can directly metabolize the ARV, tenofovir, and the presence of these bacteria ( Gardnerella vaginalis ) was associated with decreased efficacy of topical PrEP in women [ 62 ▪ ]. Furthermore, they showed that classes of bacteria in the FRT that are also commonly found in the gut, such as Prevotella spp.…”
Section: Pharmacomicrobiomics: Study Of Drug–microbiome Interactionsmentioning
confidence: 99%
“…Many types of pathogens for vaginal infections such as; candidal vaginitis, vaginal eubiosis prevention by killing dysbiotic microbes with acidic lactic acid is one of the claims often made specifically for lactobacillus strainsprobiotics, formulated with multiple or single strains. Such as (Lactobacillus plantarum, Lactobacillus fermentum, Lactobacillus rhamnosus GR-1, Lactobacillus reuteri RC-14, Lactobacillus acidophilus, L. brevis, L. gasseri, L. crispatus,) such as establishment of vaginal eubiosis by killing dysbiotic microbes, and many types of pathogens, with acidic lactic acid, have been evaluated in several randomized clinical trials that it can prevent vaginal infections, alone or as adjuncts to antibiotic therapy, and for the prevention of bacterial vaginosis [119][120][121][122].…”
Section: Prevention and Management Of Vaginal Infectionsmentioning
confidence: 99%
“…Combinations of Lactobacillus rhamnosus or Lactobacillus paracasei with Bifidobacterium longum has been used safely from 2 months before delivery until the breastfed infant was 2 months and study of Lactobacillus Fermentum CECT5716 as prevention of mastitis in breastfeeding women [136,137]. It is safe when taken by mouth appropriately many studies were orally administered; Lactobacillus is also likely safe for women to use inside the vagina [122]. To prevent the reproduction of Lactobacillus species in the environment recombinant plasmids and chromosomallymodified bacterial strains can be controlled by the use of auxotrophic mutants.…”
Section: Safety Concerns Of Lactobacillus Strainsmentioning
confidence: 99%